2005
DOI: 10.1161/circulationaha.104.516716
|View full text |Cite
|
Sign up to set email alerts
|

Occult Cardiac Contractile Dysfunction in Dystrophin-Deficient Children Revealed by Cardiac Magnetic Resonance Strain Imaging

Abstract: Background-Duchenne muscular dystrophy (DMD) is an inherited disease characterized by early onset of skeletal muscle degeneration and progressive weakness. Although dilated cardiomyopathy may occur during adolescence, it is often undetected early in its course because of physical inactivity and generalized debilitation. The purpose of this study was to apply the technique of cardiac magnetic resonance (CMR) tagging to detect occult cardiac dysfunction in young subjects with DMD by measuring myocardial strain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(105 citation statements)
references
References 35 publications
7
95
0
3
Order By: Relevance
“…32 The presence of myocardial strain abnormalities, as well as a serial decline in myocardial strain magnitude without a change in ejection fraction, has been previously reported in other forms of nonischemic cardiomyopathy. 14,[33][34][35] Our data provide evidence of similar findings in AIC subjects with reductions in regional performance in these subjects as demonstrated by low peak longitudinal (ε ιι ) and circumferential strain (ε cc ) magnitude in all segments of the myocardium. In contrast to the widespread segmental involvement demonstrated by CMR, speckle-tracking techniques by TTE demonstrated reductions limited to the anteroseptal and inferoseptal segments.…”
Section: 31supporting
confidence: 75%
See 1 more Smart Citation
“…32 The presence of myocardial strain abnormalities, as well as a serial decline in myocardial strain magnitude without a change in ejection fraction, has been previously reported in other forms of nonischemic cardiomyopathy. 14,[33][34][35] Our data provide evidence of similar findings in AIC subjects with reductions in regional performance in these subjects as demonstrated by low peak longitudinal (ε ιι ) and circumferential strain (ε cc ) magnitude in all segments of the myocardium. In contrast to the widespread segmental involvement demonstrated by CMR, speckle-tracking techniques by TTE demonstrated reductions limited to the anteroseptal and inferoseptal segments.…”
Section: 31supporting
confidence: 75%
“…This difference likely reflects the enhanced sensitivity of CMR for the detection of subtle changes in intramural contractile function, as previously reported. 33 Postcontrast myocardial longitudinal relaxation time (T 1 ) mapping constitutes a novel technique for quantifying interstitial myocardial fibrosis, 16,36 a fundamental change associated with early pathological remodeling in the course of AIC. 5 An increasing number of studies have identified diffuse myocardial fibrosis in several cardiac disease states [36][37][38] with the use of various protocols for T1 mapping 16,23,36 and in pediatric patients exposed to anthracyclines.…”
Section: 31mentioning
confidence: 99%
“…patients manifested reduced mid-ventricular and basal cross-sectional global circumferential strain using the MR tagging method [14]. The two-dimensional speckle tracking echocardiography might easily measure the strain of the myocardium with increased spatial and temporal resolution in comparison to MR tagging strain analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging was also performed at ages 18 and 25 months to evaluate the peak circumferential myocardial strain of the LV, a very sensitive measure of myocardial distress. 25 For these measurements, the magnetic resonance image of the complete LV wall was partitioned into 6 segments ( Figure 5A). At 18 months ( Figure 5B), tadalafiltreated dogs showed improved circumferential myocardial strain values than untreated dogs in the anterior segment of the interventricular septum (segment 2).…”
Section: Tadalafil Delays Cardiomyopathy In Grmd Dogsmentioning
confidence: 99%